Análisis de los radioenlaces del Gad municipal del Cantón Las Naves - Riquero Moncerrate, Gabriela Mercedes (2020)
The objective of this case study is to assess the characteristics of the radio link of the Municipal Decentralized Autonomous Government (GADM) of the canton Las Naves, province of Bolívar, evidencing that the equipment used has a life time of five years, which provide service to three sectors of the Las Naves canton, in which the number of users increased in relation to which they were originally planned. The methodology applied had a non-experimental design, with a qualitative approach, using data collection techniques such as observation, user surveys, and interviews with the technicians in charge of radio links. After analyzing the data, it was found that there are some radio link equipment exposed to climatic variations and natural conditions that decrease their useful life and obstruct visibility between one point and another, interfering with the quality of service, which also affects the increase in users, whose number exceeded the initial installed capacity. An alternative to improve the quality of service is updating equipment and expanding bandwidth.